Checks and Balances on Interpretations of Sacred Texts that Justify Violence - Bilal Masud (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
Religious teachings are understood to be against violence. But could a scholar doing a religious interpretation justify violence? One way to address this issue could be to say that religious principles place limits even on religious scholars. Hence, religious scholars cannot ignore certain generally accepted standards. Some of these standards originate in religious texts themselves. But it is not against any religious teaching, nor it is secularism, to say that standards for interpreting religious texts should be coherent with logic and shared human experience. A religion may use rational ways of thinking to make its message more intelligible to everyone and the interpretation of religious texts should also be based on such rational ways of thinking. In Islam, Imam Fakhr-ud-din Razi advocated the “use of reason all through” as qanun-i-kulli. A contemporary (empirical, rational and universal) exposition of reason is also finding its way into religious literature. For example, Mustafa Akyol (in Re-opening of Muslim minds) and Alija Izetbegović (in Islam between east and west) advocate that moral evaluations presented by religion should be combined with experiential or shared justifications for ethical practices. This combination of reason and religion could help reduce communal biases and promote peacebuilding by promoting the possibility of inter-communal understanding.